Produktivitas Karkas Domba Garut Jantan pada Pemberian Jenis Pakan dan Waktu yang Berbeda - Aslimah, S.; Yamin, M.; Astuti, D. A. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2014)
Garut sheep (GS) is one of important commodity in Indonesia. The aims of this research were to evaluate the Effect of mungbean sprouts waste and different time feeding management(morning,evening)on the carcass productivity in garut rams.In this experiment 12 male garut were used, aged 6-7 months, weighed 16.76 ± 2.09 kg (CV = 8.01 %).They were arranged into a completely randomized design with factorial 2x2 and 3 replications.Feed ration was first factor observed (R1=40% mix grass+60% concentrate and R2= 40%mungbean sprouts waste + 60% concentrate) and second factor was feeding time management, morning (M) and evening (E). The data were analyzed by analysis of variance. The results showed that there was no interaction between two main factors (P<0.05). GS with R2 treatment have slaughter weight, carcass weight and carcass fat which higher than R1. Feeding GS in the evening increased the proportion of meat. The percentages of carcass were 39.07 % inR1M;37.18%in R1E;41.99% in R2M and 42.46% in R2E. Feeding GS with mungbean sprouts increased average daily gain around 141.29 gram head/day.